Analisis Faktor-Faktor yang Mempengaruhi Minat Penggunaan LinkAja Syariah Generasi Z Kota Semarang - Utama, Kurnia Lintang (Jurnal Ilmiah Ekonomi Islam, 2024)
The research objective is to analyze and determinate to the factors about perceived ease of use, perceived usefulness, trust and knowledge riba that influence the interest in using LinkAja Syariah among 100 generation Z in Semarang City. The data used is secondary data from Badan pusat statistik and primary data collected through interviews and used kuesioner with generation Z respondents who used LinkAja Syarih in Semarang city. The data analysis method used in this research is multiple regression. The results showed that partically perceived ease of use, perceived usefulness, trust and knowledge about riba had a significant effet in influecing generation Z to used LinkAja Syariah. Simultaneously, perceived ease of use, perceived usefulness, trust and knowledge riba have a significant effect on generation Z intention to use LinkAja Syariah in Semarang City.